The Development of Web-Based Learning: The Interactive Science Website of The Topic of Animal Types for Standard Two (2) - Nik Roseli, Nik Aqel; Hamzah, Norhasyimah (Research and Innovation in Technical and Vocational Education and Training, 2022)
An interactive site developed to assist the teaching process of the educators because with the use of the site such interactivity can create a fun atmosphere at the same time being able to convey information more effectively. Therefore, this study aims to design, develop interactive sites as well to evaluate the functionality of interactive sites for the topic of Animal Types for standard two (2) s student. To develop this interactive site, design model used is the Hannafin & Peck model. Developer use qualitative methods with science teachers at Sekolah Rendah Kebangsaan Seri Jaya, Batu Pahat to identify improvements in the learning process of science subjects for the topic types of animals. The expert evaluation was done involving four (4) experts who using an expert check form instrument. Results from the findings of the study shows all experts agree that this interactive site is interesting and suitable for use by target users. Overall, the expert’s verification findings show all three designs namely information design, interaction and between the face is appropriate. In conclusion, this interactive site can be recommended to educators for use as a teaching aid which has the potential to improve student achievement in the future come.